STUDY OF HEART RHYTHM VARIABILITY OF MARTIAL ARTS DURING THE CHOICE REACTION (Physical Culture and Sport: Scientific Perspective, 2024)
The article investigates the heart rate variability (HRV) of martial artists during decision-making reactions. The study involved instructors from the martial arts department (n=4, aged 49.2±8.9 years), with 188 measurements taken (n=94 for HRV in the supine position; n=94 for HRV during a decision-making test). HRV measurements in the supine position (5 minutes duration) and during the decision-making test (4.1±0.6 minutes duration) were conducted in the morning hours each day. The study lasted for 23.5±3.5 days. Analysis of scientific-methodical literature identified HRV as an integral indicator of the functional state of the cardiovascular system and the entire organism, with sensorimotor functions being a promising direction for researching the psychophysiological characteristics of martial artists. Based on this, a mobile application "HRV SR+CR" was developed for comprehensive research on HRV and sensorimotor reactions. The mobile application "Research HRV" was used for HRV analysis. The study results showed that the developed mobile application "HRV SR+CR" allows for a comprehensive assessment of martial artists' functional state based on the dynamics of HRV and the level of decision-making reaction expression. Preliminary testing of the mobile application "HRV SR+CR" demonstrated the program's reliability. Analysis of individual respondents' results indicates the sensitivity of the measurements performed. It was determined that there are statistically significant correlations between HRV parameters and components of the decision-making reaction. High statistically significant correlations (p
Keywords: mobile applications; martial arts; heart rate variability; decision reaction